(untitled) (Bangladesh Journal of Zoology, 2015)
The study was conducted on effectiveness of different management practices of the trunk borer infestation in farmers jackfruit orchards at Kapasia upazila under Gazipur district of Bangladesh during 2009-2010. Among the ten treatments, the T5 (placing aluminium phosphide + sealed hole with bordeaux paste) ensured the highest (83.33 %) control of infestation and the highest increase in yield (51.30%) over the control. The cost: benefit of T6 (placing aluminium phosphide into the hole + sealing the hole with cow dung) (1:10.21) was higher than T5 (1: 7.75) but in terms of infestation control and total yield T5 was higher than T6. Bangladesh J. Zool. 41(2): 181-187, 2013